Reconhecimento da memória de própria experiência do princípio de semelhança na promoção de saúde de mulheres em situação de violência e vulnerabilidade - Antônio Carlos Gonçalves da Cruz (2019)
ABSTRACT Promotion of Health and Prevention of Violence demand for the praxis of autonomy. It commits itself to equalization, in a participatory context inspired by the agreement where people identify themselves by Memory of their own Experience. This is the demand that the Principle of Similarity covers. In the interest of health, by the fine threads assimilated by this principle, nets woven entangle conversely organic cohesions by consensus, in the manner of conversation wheels. Representatives of organisms animated by assimilation, they help the reinvigoration of the individuals, through reciprocal recognition from Memory of own Experience. The Principle of similarity guides Homeopathic Medicine and opens itself to the equation between violence and illness. As it strengthens organic health to cure illness, it can address violence that threatens the realization of social life. Thereby, studies about the relationship of Memory of Own Experience of the principle of similarity and communicative agility in conversation wheels may imply Homeopathic Medicine more strongly with Health Promotion and Prevention of Violence. It aims to recognize the Memory of own experience of the Principle of similarity as health promotion of women in situations of violence and vulnerability. Qualitative research was developed by collecting sixteen in-depth interviews and twelve participant observations from the chat rooms held at the Outpatient Clinic / Women's Health Promotion in Situation of Violence and Vulnerability. Thematic category content analysis was carried out. It has been found that the wheels of conversation lessen inequalities in dynamics mediated by Memory of Own Experience which manifests the Principle of Similarity. The conceptions of health as a social right and as isonomy among the organic powers are closely connected. This affinity evidences the praxis of autonomy where the Memory of Own Experience is based. Thus, the Principle of Similarity places in the same matrix the source of resources to conserve and improve health, to sanitize illnesses and to solve the violence. That basis is health itself. Gradually, it becomes available by reminiscence to the reflective subject. Through this memory he covers the perception of the different factual experiences with the assimilative knowledge of reducing strangeness and sorrow. As savvy that speaks pure agreement, in the scope of the thought in which the subject talks alone with himself, this instruction forgives the previous sensible learning. The mitigation of sorrows and the promotion of well-being on the wheels of conversation equate people insofar as they recognize each other by the same countenance, the ideal face expressing pure communication that forgives differences in remembrance of the Principle of similarity or natural agreement. On the wheels of conversation, equal subjects sympathize and discover, themselves, an adequate sense of revival, in learning with their own essences. Thus, they are more easily liberated and humanized under the influence of the best or the common good with which they share suitability, allowing us to think that failure to actualize their own improvement consists of violence and illness. So the Memory of Own Experience of the Principle of Similarity pervades the reduction of differences with which people on the wheels of conversation equalize and resubject, by self-discovery, in the scope of Health Promotion and Prevention of Violence.